2019
DOI: 10.1111/psyp.13442
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐band desynchronization reflects memory‐specific processes during visual change detection

Abstract: Recent work investigating physiological mechanisms of working memory (WM) has revealed that modulation of alpha and beta frequency bands within the EEG plays a key role in WM storage. However, the nature of that role is unclear. In the present study, we examined event‐related desynchronization of alpha and beta (α/β‐ERD) elicited by visual tasks with and without a memory component to measure the impact of a WM demand on this electrophysiological marker. We recorded EEG from 60 healthy participants while they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 34 publications
5
28
1
Order By: Relevance
“…Another study found no correlation between WM www.nature.com/scientificreports/ performance and relative alpha power in the Sternberg task (Sghirripa et al 25 ; N = 24). Better WM performance was associated, in some studies, with stronger alpha enhancement in more difficult tasks than in the easy tasks (Hu et al 19 : N = 20, r = 0.55; N = 23, r = 0.59), in other studies, however, with stronger alpha suppression in more difficult tasks (Erickson et al 26 : N = 60, r = 0.45; Fukuda et al 16 : N = 28, r = 0.48).…”
Section: Discussionmentioning
confidence: 96%
“…Another study found no correlation between WM www.nature.com/scientificreports/ performance and relative alpha power in the Sternberg task (Sghirripa et al 25 ; N = 24). Better WM performance was associated, in some studies, with stronger alpha enhancement in more difficult tasks than in the easy tasks (Hu et al 19 : N = 20, r = 0.55; N = 23, r = 0.59), in other studies, however, with stronger alpha suppression in more difficult tasks (Erickson et al 26 : N = 60, r = 0.45; Fukuda et al 16 : N = 28, r = 0.48).…”
Section: Discussionmentioning
confidence: 96%
“…Seven of 55 studies (one MEG and six EEG studies) compared at least two levels of load above 3 items. However, in four of the 7 studies the effect was neither formally tested by pairwise comparisons nor it was possible to infer the effect from the figures or other analyses (Erickson et al, 2019;Moran et al, 2010;Pahor and Jausovec, 2017;Spitzer et al, 2014). In the remaining three studies the saturation effect took place.…”
Section: Alphamentioning
confidence: 99%
“…Visual discrimination is associated with local Alpha desynchronization right after stimulus presentation (Dijk et al, 2008; Erickson et al, 2019; Hillyard et al, 1998; Sauseng et al, 2009; Zammit et al, 2018). Subsequently, it has been shown in several perceptual experimental modalities that a decrease in the Alpha-Beta band is linked to better stimulus perception (Griffiths et al, 2019).…”
Section: Discussionmentioning
confidence: 99%